Novel therapeutic approaches in primary hyperoxaluria. (2nd October 2018) - Weigert, Alexander; Martin-Higueras, Christina; Hoppe, Bernd
ABSTRACT: Introduction : Currently, three types of primary hyperoxaluria (PH I–III) are known, all based on different gene-mutations affecting the glyoxylate metabolism in the liver. Disease hallmark is an increased endogenous oxalate production and thus massively elevated urinary excretion of oxalate and other type-specific metabolites. Hyperoxaluria induces the formation of calcium-oxalate kidney stones and/or nephrocalcinosis. In addition to that, a chronic inflammasome activation by hyperoxaluria per se, often leads to an early deterioration of kidney function, regularly resulting in end-stage renal disease (ESRD) at least in patients with type I PH. Except for vitamin B6 treatment in PH I, therapeutic regimen nowadays consists only of supportive measures, like significantly increased fluid intake and medication increasing the urinary solubility like alkaline citrate. Areas covered : Disease burden can be severe, and both clinicians and scientist are eager in finding new therapeutic approaches. The currently ongoing clinical studies and promising research in this field are reported in this paper. To present a complete overview, we searched electronic databases, like Clinical trial gov, National Center for Biotechnology Information PubMed, congress reports, press releases and personal information acquired at congresses and conventions. Searches were conducted using the following medical headings: (primary) hyperoxaluria, PH, therapy, treatment and research. Expert opinion : There is light on the horizon that new treatment options will be available in due time, as there are several promising therapeutic agents currently under investigation, some being at the first levels of drug development, but some already in ongoing clinical trials (phase I-III).